Enhancement in the Catalytic Properties of CotA Laccase from Bacillus pumilus via High-Throughput Screening Using Malachite Green as a Pressure - Xiufang Li; Jieru Tian; Xidong Ren; Junming Wang; Xinli Liu (Microorganisms)
Bacterial laccase exhibits substantial application potential in various fields. In this study, we constructed a mutation library of CotA laccase from Bacillus pumilus using error-prone PCR, and we performed four rounds of enrichment screening under malachite green (MG) pressure. The results demonstrated that the proportions of the four selected mutant strains were significantly increased. The enzyme activities of the four final mutants PW2, PW5, PW4G, and PW6 were 94.34, 75.74, 100.66, and 87.04 U/mg, respectively, representing a significant increase of approximately 2- to 3-fold compared to the wild-type CotA laccase. Notably, PW4 exhibited significantly improved thermal stability at 90 °C and pH tolerance at pH 12.0. Homology modeling analysis revealed that alterations in the amino acid sequence rendered the spatial structure of the enzyme’s catalytic site more favorable for substrate binding. For instance, the substitution of T262A in PW2 and V426I in PW4 shortened the side chains of the amino acids, thereby enlarging the substrate-binding cavity. The G382D mutation in PW2 and PW5 may induce altered protein conformation via spatial steric hindrance or electrostatic interactions, consequently impacting enzyme activity and stability. These findings provide valuable insights for enhancing the industrial application of bacterial laccase.